2020
DOI: 10.1210/jendso/bvaa046.2162
|View full text |Cite
|
Sign up to set email alerts
|

SAT-LB15 24-Month Efficacy and Safety of Once Weekly and Every Other Week Administration of GX-H9, Hybrid FC-Fused Long-Acting Human Growth Hormone: A Phase 2 Study in Children With Growth Hormone Deficiency

Abstract: Objectives GX-H9 is a long-acting form of recombinant human GH under clinical development for both adults and children with GHD. In this report, 24-month efficacy and safety of once weekly and every other week (EOW) administration of GX-H9 were evaluated, in addition to Genotropin® switch-ability to GX-H9 after 12-month of treatment. Methods Subjects were randomly assigned to receive either one of three doses of GX-H9 (0.8 mg/kg/week, 1.2 mg/kg/week or 2.4 mg/kg every other week) or 0.03 mg/kg/day of Genotropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Somatrogon is a long‐acting GH fused to three copies of the carboxyl‐terminal peptides derived from the human chorionic gonadotropin, currently used for treating pediatric GHD as a once‐weekly subcutaneous injection (Deal et al, 2022 ; Horikawa et al, 2022 ). Other versions of fusion proteins are currently under development at various stages of clinical trials: GX–H9 (Genexine and Handok), a long‐acting GH fused to a hybrid Fc which consists of noncytolytic IgD and IgG4 (Ku et al, 2018 ; Malievskiy et al, 2020 ); JR‐142 (JCR Pharmaceuticals), a long‐acting GH fused to a modified HSA (Japan Registry of Clinical Trials, 2021); LAPS rhGH (HM10560A; Hanmi Pharmaceutical Co), a long‐acting GH conjugated to recombinant immunoglobulin G4 Fc fragment ( clinicaltrials.gov , HM10560A).…”
Section: Long‐acting Gh Pharmaceutical Formulation...mentioning
confidence: 99%
“…Somatrogon is a long‐acting GH fused to three copies of the carboxyl‐terminal peptides derived from the human chorionic gonadotropin, currently used for treating pediatric GHD as a once‐weekly subcutaneous injection (Deal et al, 2022 ; Horikawa et al, 2022 ). Other versions of fusion proteins are currently under development at various stages of clinical trials: GX–H9 (Genexine and Handok), a long‐acting GH fused to a hybrid Fc which consists of noncytolytic IgD and IgG4 (Ku et al, 2018 ; Malievskiy et al, 2020 ); JR‐142 (JCR Pharmaceuticals), a long‐acting GH fused to a modified HSA (Japan Registry of Clinical Trials, 2021); LAPS rhGH (HM10560A; Hanmi Pharmaceutical Co), a long‐acting GH conjugated to recombinant immunoglobulin G4 Fc fragment ( clinicaltrials.gov , HM10560A).…”
Section: Long‐acting Gh Pharmaceutical Formulation...mentioning
confidence: 99%
“…GX-H9 is a rhGH fused to the Fc portions of IgD and immunoglobulin G 4. Phase 2 dose-find-ing trial in children with GHD reported a comparable efficacy and safety of GX-H9 to daily rhGH [27]. Finally, Somavartan (VRS-317) from Versartis reached a phase 3 study level in children with GHD but was no longer developed after the study proved it to be inferior to daily rhGH in increasing HV and height SDS [28].…”
Section: Gh Fusion Proteinsmentioning
confidence: 99%
“…Оптимальною стартовою дозою препаратів рГР для лікування хворих на СБНГР є 0,035 мг/кг на добу з подальшим підвищенням дози до 0,05 мг/кг на добу при незадовільному ростовому ефекті. Тривале лікування препаратами рГР в дозі 0,035 мг/кг на добу та 0,05 мг/кг на добу є ефективним і безпечним [70].…”
unclassified